Strategies for effective dissemination of project outcomes. - Southwell, Deborah; Gannaway, Deanne; Orrell, Janice; Chalmers, Denise; Abraham, Catherine (Commonwealth of Australia, 2005)
The aim of this project was to systematically investigate Australian and international learning and teaching grant schemes and their outcomes to determine strategies the Carrick Institute might employ to maximise the likelihood of achieving large-scale change in teaching and learning across the Australian higher education sector, especially through its grants program. The project has identified a number of conditions that have been shown to be effective in achieving dissemination of project outcomes and that engage the multiple levels of the higher education sector. It has recommended strategies for the Carrick Institute and leaders of institutions to manage multiple innovative strategies that impact on the culture and practices of universities and their departments as well as on the practices of individual academics. [Introduction]